Effect of intravenous almitrine on intubation or mortality in patients with COVID-19 acute hypoxemic respiratory failure: A multicentre, randomised, double-blind, placebo-controlled trial. (October 2022) - Kalfon, Pierre; Payen, Jean-François; Rousseau, Alexandra; Chousterman, Benjamin; Cachanado, Marine; Tibi, Annick; Audibert, Juliette; Depret, François; Constantin, Jean-Michel; Weiss, Emmanuel; Remerand, Francis; Freund, Yonathan; et al.
Summary: Background: Severe hypoxemia in patients with COVID-19 pneumonia might result from hypoxic pulmonary vasoconstriction, contributing to ventilation/perfusion (V/Q) mismatch. Because almitrine improves V/Q, it might reduce the risk for mechanical ventilation (MV) in such patients. Our primary objective was to determine the effect of almitrine on the need for MV at day 7. Methods: In a randomised double-blind placebo-controlled trial involving 15 ICUs, patients hospitalized for COVID-19 pneumonia and experiencing acute hypoxemic respiratory failure were randomly assigned to receive 5 days of intravenous low-dose (2 µg.kg −1 .min −1 ) almitrine or placebo. The primary outcome was endotracheal intubation for MV or death within 7 days after randomisation. Secondary outcomes included in-hospital mortality, 28-day mortality, number of ventilator-free days, number of days in the ICU and the hospital, and treatment discontinuation for pre-specified adverse effects. This trial was registered with ClinicalTrials.gov, NCT04357457. Findings: Between September 3, 2020 and September 25, 2021 181 patients were enrolled and randomly assigned to almitrine (n=89) or placebo (n=92). 179 patients (excluding two who withdrew from the study) were included in the intention-to-treat analysis (mean age: 60·1 years; 34% women) and analyzed. On day 7, the primary endpoint occurred in 32 patients assigned to almitrine (36%) and in 37 patients assigned to placebo (41%), for a difference of –4·3% (95% confidence interval: −18·7% to 10·2%). Secondary outcomes (28-day mortality, in-hospital mortality, ventilator-free days at day 28, days in the ICU and the hospital, and treatment discontinuation for pre-specified adverse effects) did not differ between the two groups. Interpretation: In patients with COVID-19 acute hypoxemic respiratory failure, low-dose almitrine failed in reducing the need for MV or death at day 7. Funding: Programme Hospitalier de Recherche Clinique (PHRC COVID 2020) funded by the French Ministry of Health, Les Laboratoires Servier (Suresnes, France) providing the study drug free of charge.